An effectiveness asset disposal towards fixed asset management at Petronas Dagangan Berhad / Nurshazwani Sabli - Sabli, Nurshazwani (Faculty of Business and Management, 2009)
Asset disposal in fixed asset management is an accounting process that seeks to track fixed assets for the purposes of financial accounting, preventive maintenance, and theft deterrence asset belonging. This applies to all industries because doing so makes the workplace more productive. Without fixed asset management, the equipment and resources of the company are not used both effectively and efficiently. The issues that I would like to highlight in this study is regard whether this company adapt the actual theories of fixed asset management in their operation and how effective the company’s asset disposal operates toward company performance. The data of this study are gathered from both primary and secondary data. It has been identified in the findings that the company has adapted the actual theories of asset management in their operation. Base on the result of this study, some recommendation has been proposed which hopefully can help them to improve their business performance in the future.